Institutions and demographic responses to shocks: Württemberg, 1634-1870 - Timothy W. Guinnane; Sheilagh Ogilvie (Yale University, Economic Growth Center, 2008)
Simple Malthusian models remain an important tool for understanding pre-modern demographic systems and their connection to the economy. But most recent literature has lost sight of the institutional context for demographic behavior that lay at the heart of Malthus's own analysis. This paper estimates a short-run version of a Malthusian model for two Württemberg communities from 1646 to 1870. Württemberg differed institutionally from the northwest European societies analyzed in previous studies. The impact of institutional differences shows clearly in differing demographic reactions to economic shocks. Mortality was less sensitive to shocks than one would expect, while nuptiality was especially sensitive.
Keywords: N33; J10; 330; Malthusian models; mortality; fertility; nuptiality; guilds